State driven vicious cycles of conflict in eritrea : a constructivist analysis - Afewerky, Rahel Kessete (My University, 2019)
Bu makale Eritre’yi kısır çatışma döngüsü bataklığına sokan dengesizliği araştırmakta ve günümüzde altında yatan sebeplere ve sonuçlara odaklanmaktadır. Bu çatışmalar, devletin değişmeyen tecritci politikaların şemsiyesi altında egemenliğini koruduğunu varsaydığı katı duruşu ile desteklenmiş, hızla bozulan ekonomik koşullar, hayal kırıklığına uğramış gençliğin göç akınına eşlik etmiştir. Bu nedenle, bu çalışma, herhangi bir rekabet politikasını zedeleyecek, gücü manipüle etme mekanizmaları olarak kullanılan olağanüstü hal ve savaş durumlarının ortaya çıkmasının sürekliliğini açıklamaktadır. Çalışma, gösterilen çabaların uzun süredir çatırdayan rejiminin sona ermesine yol açan başarısızlığını açıklamakta ve devlet tarafından yürütülen çatışmaların üstesinden gelmesi için yeni bir konstüktivist vizyona acil ihtiyaç duyulduğunu öne sürmektedir.

This paper examines the instability boggling Eritrea into the mires of vicious cycles of conflict by focusing on the core causes and consequences of present-day mishaps. These conflicts indwelled with the rigid stance of the state assuming to protect its sovereignty under the umbrella of unwavering isolationist policies have manifested to be a price it can no longer afford as its fast-dwindling economic stance complements the influx migration of frustrated youth. This study, therefore, stands to explicate the unfolding perpetuation of the state of emergencies and genesis of war instrumentalized as the mechanisms of manipulating power to mutilate any competitive politics. The study construes the failure of impeded efforts that could have had decisively contributed to the demise of the long crumbling regime, and adheres to promote the immediate necessity for a new vision in a countenance of constructivist auspices to override the state-driven conflicts.
Keywords: Eritre Constructivism; Eritrea; International relations; Kısır döngü; Konstrüktivizm; Uluslararası ilişkiler; Vicious circle